Green supplier selection based on CODAS method in probabilistic uncertain linguistic environment - Wei, Cun; Wu, Jiang; Guo, Yanfeng; Wei, Guiwu (Technological and Economic Development of Economy, 2021)
Probabilistic uncertain linguistic sets (PULTSs) have widely been used in MADM or MAGDM. The CODAS method, which is a novel MADM or MAGDM tool, aims to acquire the optimal choice which have the largest Euclidean & Hamming distances from the NIS. This paper designs the probabilistic uncertain linguistic CODAS (PUL-CODAS) method with sine entropy weight. Finally, a numerical example for green supplier selection is given and the obtained results are compared with some existing models. First published online 05 February 2021